Application of The Sales and Purchase Program Using The Rapid Application Development Model - Sitompul, Dian Novianti; Rahmatika, Ahmad; Sari, Indah Purnama (Al'Adzkiya, 2023)
The development of information technology is currently growing rapidly and rapidly, which is supported by one of the means, namely the existence of a computer. Of course, a computer that has been equipped with a certain application is used to help facilitate human work in managing the data of an organization or company so that results are accurate and as needed. The results of observations that have been made indicate that there are sales and purchasing activities that still use a manual system, one of which is at a clothing store. Starting from processing goods data, difficulty checking stock, purchasing transactions, sales transactions, and storing other data related to all types of activities, so that it can cause losses for shop owners, errors in recording and inaccurate reports made. Judging from the large number of transactions made at clothing stores, a faster and more accurate information system is needed. Therefore, the authors created a computerized program design using the Microsoft Visual Basic.net programming language and MySQL database, so that information and activities that occur can be carried out quickly and accurately. The method used in designing this program uses the Rapid Application Development (RAD) model. This RAD model is an adaptation of the high-speed version of the waterfall model for the development of each software component. The results achieved from the discussion of this theme are in the form of ready-to-use sales and purchasing program applications. In this case, the use of application programs is the best solution for solving existing problems, and with the use of application programs an effective and efficient activity can be achieved in supporting activities, especially for dealing with sales and purchasing problems.